Cladistic methods to analyze adaptation - Cigliano, Maria Marta (2000)
Cladograms obtained independently of theories about evolutionary processes, e.g., adaptation, can be used to test such theories. In this paper, we briefly review the steps to be followed in a cladistic approach to the study of adaptation, namely, character mapping and optimisation of binary and multistate characters, and sister group comparisons. Two case studies are presented to exemplify this approach, one dealing with grasshoppers (Orthoptera: Acrididae) and the other with weevils (Coleoptera: Curculionoidea).